Reconfiguring health purchasing for universal health coverage: insights from Nepal with relevance to low- and middle-income countries - Sriram, Shyamkumar; Adhikari, Saroj; Saud, Bhuvan (Frontiers in Public Health, 2025)
Nepal’s transition to federalism and the rollout of the National Health Insurance Program (NHIP) marked critical steps toward universal health coverage. Yet, structural misalignments between health financing policies and purchasing practices persist, weakening the effectiveness of these reforms. Strategic purchasing—a key lever in health financing—has the potential to improve system efficiency, equity, and responsiveness by actively allocating pooled funds based on population needs, provider performance, and service value. However, in Nepal, legacy practices such as line-item budgeting, fragmented programmatic funding, and overlapping institutional roles hinder the adoption of this approach. The Ministry of Health and Population continues to play simultaneous roles as policymaker, purchaser, and provider, weakening accountability and the purchaser’s autonomy. Public providers are funded through both historical budgets and reimbursement schemes, diluting incentives for performance. Moreover, NHIP’s purchasing decisions are not guided by health technology assessments or cost-effectiveness analysis, raising concerns about the allocative efficiency of the benefit package. This Perspective argues that Nepal’s health financing reforms require institutional realignment, clearer role demarcation, and stronger contractual mechanisms to support strategic purchasing. Drawing on both national experience and international frameworks, it highlights the systemic disconnects and offers a way forward for embedding strategic purchasing into Nepal’s health financing architecture. By correcting these foundational misalignments, Nepal can better leverage public resources to deliver high-quality, equitable care, advancing the goals of federalism and universal health coverage simultaneously.